Production of protein bars with Nile tilapia protein concentrate - SOUZA, Herivelto Beck de; MEDINA, Leone de Souza; TORRES, Thais Patricio; XAVIER, Débora Tatyane Oliveira; NASCIMENTO, Jéssica Luciane; SILVA, Diego Rangel da; OLIVEIRA, Gislaine Gonçalves; MATIUCCI, Marcos Antonio; FEIHRMANN, Andresa Carla; SIGNOR, Altevir; SOUZA, Maria Luiza Rodrigues de (Food Science and Technology, 2024)
Commercial protein bars such as whey protein bars (New Millen® protein complex premium) are consumed worldwide and are usually made with whey as a protein source. Fish protein concentrate (FPC) is an alternative protein of animal origin with a different amino acid profile and fatty acid composition and can be produced from mechanically separated meat (MSM) of Nile tilapia (Oreochromis niloticus). This study investigated FPC for its nutritional characteristics and microbiological quality for the manufacture of protein bars. The FPC-enriched bars presented a potential profile of essential fatty acids for human consumption. The sensory evaluation showed good acceptance scores, with no differences from the control (commercial product) and high purchase intention. The inclusion of 5.3% of FPC in the protein bars with different flavors may be a promising alternative to produce a high nutritional value product for human consumption, besides favoring the sustainability of the fish supply chain.